Analisis Pengelolaan Air Limbah Domestik Berbasis Instalasi Pengelolaan Air Limbah (IPAL) Kota Batam - M Faiz Salekhan Aqilla; Teuku Afrizal (Journal of Management and Public Policy, 2026)
Water pollution caused by domestic wastewater discharge has become an increasingly complex environmental problem, particularly in urban areas experiencing rapid population growth and development activities. Batam City, as an industrial and trade hub, faces increasing volumes of domestic wastewater that may potentially degrade water quality if not properly managed. Therefore, an integrated domestic wastewater management system through a Wastewater Treatment Plant (WWTP) is required. This study aims to analyze domestic wastewater management based on WWTP in Batam City and to identify the driving and inhibiting factors affecting its management process. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The analysis applies the POAC management theory (Planning, Organizing, Actuating, Controlling)to examine the management process of domestic wastewater, and the PRECEDE–PROCEED model to identify the driving and inhibiting factors influencing the management system. The results show that domestic wastewater management based on WWTP in Batam City has been supported by planning and institutional involvement from the local government and the Batam Indonesia Free Zone Authority (BP Batam). However, several challenges remain, including limited WWTP service coverage, low household connection to the centralized wastewater system, and limited coordination among institutions in monitoring wastewater management. In addition, community awareness, infrastructure availability, and regulatory support are factors influencing the management process of domestic wastewater in Batam City. This study indicates that domestic wastewater management based on WWTP in Batam City still faces various challenges in planning, organizing, actuating, and controlling aspects. Therefore, strengthening institutional coordination, expanding WWTP service coverage, and increasing public awareness are necessary to support sustainable urban environmental quality.